Couchsurfing with Bateson: An ecology of digital platforms. Issue 7 (July 2022) - Mikołajewska-Zając, Karolina; Márton, Attila; Zundel, Mike
Digital platforms radically alter socio-economic and organizational patterns. In an ecological sense, they enable the rapid extension of tolerance limits by digitally scaling variables such as the availability of accommodation or labour. However, such maximization of specific variables in a complex ecology bears the danger of pathological runaway patterns. In our paper we draw on the work of Gregory Bateson to outline an analytical approach for the study of digital platforms as ecological phenomena, focusing on the effects of digitalization on the context in which platforms operate. To study such meta-patterns, we elaborate three interrelated concepts: stress, adaptation and budgets of flexibility. We exemplify these ideas through a longitudinal study of the early digital platform Couchsurfing and develop implications for our understanding of technology and organization.